Trading Off Tax Distortion and Tax Evasion - Wolfram F. Richter; Robin Boadway (Center for Economic Studies and ifo Institute (CESifo), 2001)
Tax evasion is modeled as a risky activity and integrated into a standard problem of optimal tax design. It is shown that there is a trade off between reducing tax evasion and reducing tax distortion. Thus it is efficient to supplement a broad-based wage tax by a tax on specific consumption if the former is evaded and the latter not. The optimal tax structure can be characterized by an explicit formula.
Keywords: 330; Tax evasion; risk-taking; optimal taxation